2018
DOI: 10.15760/comminfolit.2018.12.2.4
|View full text |Cite
|
Sign up to set email alerts
|

A Multicultural Approach to Digital Information Literacy Skills Evaluation in an Israeli College

Abstract: Information literacy is an essential proficiency for success in academic studies, yet many first-year students find it hard to use information sources efficiently and to develop academic information literacy. This study reports findings from first-year students' selfestimation of their information skills according to two information literacy models (Shapiro & Hughes, 1996; Ng, 2012) and presents interesting insights on the differences between the multicultural and multilingual student groups in the study's pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
0
16
0
2
Order By: Relevance
“…Similar studies on informational skills in different contexts come from Townsend, Hofer, Hanick, & Brunetti (2016); Pieterse, Greenberg, & Santo (2018), Klucevsek (2017); Tewell (2015); Hinchliffe, Rand, & Collier (2018); and Holliday (2017). The results of the results have similar to acquire information skills.…”
Section: Informational Competenciesmentioning
confidence: 76%
See 1 more Smart Citation
“…Similar studies on informational skills in different contexts come from Townsend, Hofer, Hanick, & Brunetti (2016); Pieterse, Greenberg, & Santo (2018), Klucevsek (2017); Tewell (2015); Hinchliffe, Rand, & Collier (2018); and Holliday (2017). The results of the results have similar to acquire information skills.…”
Section: Informational Competenciesmentioning
confidence: 76%
“…In the study by Pieterse et al (2018), the informants are students of the first year studying Hebrew and Arabic. It is found that students have a good level of information.…”
Section: Informational Competenciesmentioning
confidence: 99%
“…Little data exist, however, on the level of performance of Arab students in the ICT-enriched learning environment. Of the recently conducted studies, Zidan and Ganayem (2018) and Pieterse et al (2018) claimed that most of the Arab-speaking graduates had basic ICT skills to continue their education. Pieterse et al (2018) argued, however, that Arab study participants required more mediation in acquiring information literacy skills than their Jewish counterparts.…”
Section: A Brief Characteristic Of the Learning Habits Of Arab School And Tertiary Studentsmentioning
confidence: 99%
“…En esta vertiente se muestra que normalmente los instrumentos de evaluación contienen un nivel de confianza aceptable, ya que su aplicación tiene fines diagnósticos de entrada y salida sobre niveles de ALFIN. También, se observan investigaciones que logran implementar instrumentos para evaluar y desarrollar ALFIN en estudiantes (Eastman et al, 2018;Markowski, McCartin, y Evers, 2018;Pieterse, Greenberg, y Santo, 2018; Tong y Moran, 2017; Tecce, Grant, Lee y Neuman, 2018; Toledo y Maldonado-Radillo, 2015; Yeager y Pemberton, 2017). Esta vertiente se inspira en los principios del modelo Big6 para la enseñanza de ALFIN, que implica seis etapas para la resolución de problemas de información: i) definición de la tarea, ii) estrategias de búsqueda de información, iii) localización y acceso, iv) uso de la información, v) síntesis y vi) evaluación (Baji, Bigdeli, Parsa, y Haeusler, 2018), y para el diseño de instrumentos para evaluar de ALFIN (Foo et al, 2014;Foo, Majid y Chang, 2017), donde se muestra la importancia de elaborar un programa a implementar en la educación básica para atender la problemática de infantes con exposición a la Internet mucho antes de la educación formal y donde se pretende que, a través de acciones de ALFIN, cambien el rumbo de la construcción de conocimientos para su propio bien.…”
Section: Formas De Implementación De Programas De Alfin En Educaciónunclassified